A simple spreadsheet program for calculating mass attenuation coefficients and shielding parameters based on EPICS2017 and EPDL97 photoatomic libraries. (December 2020) - Hila, Frederick C.; Amorsolo, Alberto V.; Javier-Hila, Abigaile Mia V.; Guillermo, Neil Raymund D.
Abstract: A spreadsheet program for calculating mass attenuation coefficients and other shielding parameters was built. The program can choose its libraries from ENDF/B-VIII (EPICS2017) or ENDF/B-VI.8 (EPDL97) photoatomic cross sections. Using MS Excel extensions, cubic spline, one way spline, and linear interpolations were used on a log-log scale. Good agreements were shown between both libraries and XCOM generated mass attenuation coefficients in most elements from Z = 1 to Z = 100 and in most energies considered. However, there were significant differences for some heavy elements at low photon energies. The program was also validated by multi-elemental material results obtained by XCOM, by others in literature, and by the Phy-X/PSD, all with good agreements. Therefore, the program is a versatile tool especially in the validation of photon shielding parameters calculated via the Monte Carlo method. Highlights: A spreadsheet program was built for photon shielding calculations. The program can calculate μ m, σ T, σ e, Z e f f, and N e f f The EPICS2017 and EPDL97 photoatomic libraries were used as basis. Validations with XCOM and results from literature were made. Microsoft Excel interpolation extensions were used on log-log scales.